185k views
4 votes
Solve 3x - 9x + 7 - 3 = -8.
also if u explain ill give you most brainy

Solve 3x - 9x + 7 - 3 = -8. also if u explain ill give you most brainy-example-1
User Zakinster
by
4.8k points

2 Answers

3 votes

Steps To Solve:

3x - 9x + 7 - 3 = -8

Combine Like Terms.

-6x + 4 = -8

Subtract 4 to both sides.

-6x + 4 - 4 = -8 - 4

Simplify.

-6x = -12

Divide -6 to both sides.

-6x/-6 = -12/-6

Simplify.

x = 2

--------------

Option C is the correct answer.

--------------

Best Regards,

Wolfyy :)

User RichGoldMD
by
5.4k points
4 votes

Answer:

2

Explanation:

add the like terms

3x - 9x + 7 - 3 = -8 ➡ -6x +4 = -8

-6x = -8 -4 ➡ 6x = 12 and x = 2

User MicBehrens
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.